Analysis of Ni, Cu, and Fe in Loose Cosmetic Products: A Preliminary Dermal Exposure and Health Risk Assessment - Agnieszka Berdowska; Katarzyna Bandurska; Joanna Kończyk; Iwona Zawierucha (Toxics, 2026)
Loose cosmetic products are widely used in everyday makeup application; however, they may constitute a source of consumer exposure to metals present either intentionally as structural mineral pigments or unintentionally as contaminants derived from raw materials. The aim of this study was to quantitatively determine the concentrations of nickel, copper, and iron in loose facial cosmetics (including face powders, contouring products, and eyeshadows) available on the Polish market and to evaluate the potential human health risks. Following validated microwave digestion, the samples were analyzed using microwave plasma–atomic emission spectrometry (MP-AES). Non-carcinogenic and carcinogenic health risks were assessed for dermal exposure by calculating the Hazard Quotient (HQ), Hazard Index (HI), and lifetime cancer risk (LCR). The analyzed metals were detected in the majority of the tested products. Nickel was not detected in four cosmetic samples, whereas its concentration in the remaining products ranged from 0.45 to 37.57 mg/kg. Copper concentrations were between 0.83 and 35.39 mg/kg, while iron concentrations varied from 0.03 × 103 to 109.56 × 103 mg/kg. The calculated HQ and HI values (maximum HI = 8.91 × 10−5) were well below 1, indicating no significant non-carcinogenic health risk. The estimated lifetime cancer risk for nickel was within the safe range (5.63 × 10−12 to 8.28 × 10−9). Chronic dermal exposure to the analyzed metals is therefore unlikely to pose either systemic toxic or carcinogenic risks to consumers. However, the detected levels of nickel and copper in the samples with the highest concentrations may trigger local allergic reactions in sensitized individuals. These findings highlight the importance of monitoring the purity of mineral raw materials used in cosmetic production.